2012
DOI: 10.1159/000339206
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Serum Profile in Patients with Viral Liver Cirrhosis

Abstract: Objective: Our main aim was to investigate the serum lipid levels in a series of patients with liver cirrhosis of viral origin. Subjects and Methods: The study comprised 90 patients, 60 with viral liver cirrhosis, equally divided between hepatitis virus C (HCV) and B (HBV) etiologies, and 30 control patients with no known liver pathology. Patients were investigated during a 5-year period in the 1st Medical Clinic of the Emergency County Hospital of Craiova, Romania. The following series of serum lipid paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Hypocholesterolemia and hypotriglyceridemia are both significantly associated and correlated with the Child-Pugh and MELD prognostic criteria. These findings were consistent with previous studies that showed changes in lipid metabolism in advanced stages of cirrhosis (1,13,21) .…”
Section: Discussionsupporting
confidence: 94%
“…Hypocholesterolemia and hypotriglyceridemia are both significantly associated and correlated with the Child-Pugh and MELD prognostic criteria. These findings were consistent with previous studies that showed changes in lipid metabolism in advanced stages of cirrhosis (1,13,21) .…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies proved that lipid metabolism was severely impaired in liver cirrhosis originating from hepatitis C and B viruses (Vere et al, 2012), implying that the process of lipid metabolism was attenuated during liver cirrhosis. Surprisingly, fatty acid metabolism was activated at 3 weeks and slightly inhibited at 6 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, low TC level was reported to be in close association with severe liver fibrosis in these patients. It is implied that liver functional reserve became poorer with the decrease of TC (Vere et al, 2012; Wang et al, 2014). Several studies have shown low serum TC level and low serum HDL level were associated with worse disease-free survival and overall survival in HCC patients undergoing surgical hepatectomy, breast cancer patients, colorectal cancer patients receiving adjuvant chemotherapy, and non-small-cell lung patients with EGFR mutations (Lee et al, 2016; Li et al, 2016; Wang et al, 2016; Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%